An Update on Antioxidative Stress Therapy Research for Early Brain Injury After Subarachnoid Hemorrhage - Lin, Fa; Li, Runting; Tu, Wen-Jun; Chen, Yu; Wang, Ke; Chen, Xiaolin; Zhao, Jizong (Frontiers in Aging Neuroscience, 2021)
The main reasons for disability and death in aneurysmal subarachnoid hemorrhage (aSAH) may be early brain injury and delayed cerebral ischemia. Despite studies reported and progressed when delayed cerebral ischemia well-treated clinically, the prognosis is not well-improved. According to the present situation, we regard early brain injury as the main target of future researches, and one of the key phenotype-oxidative stress may be called for attention in early brain injury after laboratory SAH. We summarized the research progress and updated the literature that has been published about the relationship between experimental and clinical SAH-induced early brain injury and oxidative stress in PubMed from January 2016 to June 2021. Many signaling pathways are related to the mechanism of oxidative stress in early brain injury after SAH. Several antioxidative stress drugs were studied and showed a protective response against early brain injury after SAH. The systematical study of antioxidative stress in early brain injury after laboratory and clinical SAH may supply us with new therapies about SAH.